PENINGKATAN DISOLUSI ROSUVASTATIN CALSIUM DARI SEDIAAN TABLET DENGAN TEKNIK LIQUISOLID DAN PEMBENTUKAN KOMPLEKS INKLUSI - Sutiswa, Shandra Isasi; Cahyati, Yeyet; Mudhakir, Diky (Jurnal Riset Kefarmasian Indonesia, 2019)
Rosuvastatin calcium is a salt form of rosuvastatin with antilipidemia activity. Rosuvastatin Calcium classified in class two of Biopharmaceutics Clasification System (BCS) has low solubility in water (17.96 mg / L) and high permeability. Based on this, rosuvastatin calcium needs to be formulated appropriately in order to produce high bioavailability and maximum therapeutic effect. The bioavailability of BCS 2 drug is determined by the dissolution rate of the drug in gastrointestinal fluid so that a technique is needed in formulating the drug. This study aims to develop a formulation technique for rosuvastatin calcium tablets through liquisolid technique and formation of inclusion complexes with β-cyclodextrin in order to increase the rate of dissolution. Tablet formulation with liquisolid technique was made with a concentration of 10% rosuvastatin calcium in propylene glycol, with a ratio of US2® (carrier) and Aerosil 200 (coating) made with a ratio of 10: 1 and 20: 1. In addition to the formulation with liquisolid technique, formulations were also carried out with the complex inclusion technique of rosuvastatin calcium-β-cyclodextrin using kneading method and freeze drying method with a mol ratio of 1: 1 and 1: 2. The liquisolid system and inclusion complexes formed were characterized using FTIR and SEM. Characterization results indicated changes in the form of polymorphous rosuvastatin calcium. Tablet formulations were made by direct compression using a liquisolid system and an inclusion complex equivalent to 10 mg of rosuvastatin calcium. Based on the results of the ANOVA statistical test and further LSD tests showed that calcium rosuvastatin tablets made with liquisolid and inclusion complexes can increase the dissolution rate compared to pure rosuvastatin calcium tablets and inovator rosuvastatin calcium tablets. The highest dissolution rate was produced by liquisolid R20: 1 tablet at 60 minutes at 85.53 ± 1.02% in an enzyme-free simulated gastric fluid dissolution medium and 110.02 ± 1.71% in an enzyme-free simulated intestinal fluid dissolution medium.